PENERAPAN STRATEGI SEGMENTING, TARGETING, POSITIONING (STP) DAN BRANDING DALAM MENINGKATKAN VOLUME PENJUALAN: STUDI KASUS PADA SALES MOTORIS PT MADUSARI NUSAPERDANA CABANG BANDUNG - Mutia, Linda; Rahmi, Cinta (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The competitive Indonesian FMCG processed food industry, particularly in Bandung, challenges companies to maintain sales volume in a fragmented market with local competitors. This study analyzes the application of STP (Segmenting, Targeting, Positioning) strategy and branding by the motorized sales team of PT Madusari Nusaperdana Bandung Branch to increase sales volume. Using a descriptive qualitative approach, purposive sampling targeted 2 area coordinators, 5 experienced salespeople, and 10 strategic outlets from a population of 15-20 sales personnel. Data was collected through in-depth interviews, participant observation, and documentation, analyzed using the Miles and Huberman interactive model (reduction, presentation, triangulation verification). The results show comprehensive geographic-demographic-psychographic segmentation, selective targeting of Segment A/B outlets near schools/residential areas, practical-hygienic food positioning, and consistent Kimbo branding through sales as brand ambassadors. This synergy results in sales efficiency, high retail conversion, premium pricing, as well as B2B/B2C loyalty. The conclusion emphasizes that STP-branding integration is a critical success factor for processed food distribution through operational field execution.